Memes como evolución de los medios de expresión social. Caso Lenin Moreno - Burbano Montero, Vilma Lorena (2021)
Memes have now become a worldwide trend and their use grows every time, reaching the point of getting involved with social, economic and political issues. The main objective of the case study was to analyze memes as an evolution of the means of social expression: Lenin Moreno case. That style of content became widely shared during the Lenin Moreno government. The development of the theoretical framework is based on bibliographic sources of the topic of interest. In addition, a mixed approach methodology was proposed, with a special observation of the most popular memes that dealt with the former president in 2019, and of a survey carried out on 50 citizens, between 18 to 40 years old, with a bank of 10 questions, which allowed obtaining first-hand information. According to the analytical-synthetic method carried out, it is concluded that memes are a clear example of the evolution of social expressions, but since this type of publication was created to generate humor, but on many occasions the information displayed may be false. And that memes were so popular during Moreno's term because of their bad way of running the government and addressing the nation.